Neurobehavioral Symptoms in Community-Dwelling Adults With and Without Chronic Traumatic Brain Injury: Differences by Age, Gender, Education, and Health Condition - Juengst, Shannon B.; Nabasny, Andrew; Terhorst, Lauren (Frontiers in Neurology, 2019)
Neurobehavioral symptoms after Traumatic Brain Injury (TBI) are prevalent, persist for many years, and negatively affect long-term health, function, and quality of life. Symptoms may differ based on age, gender, education, race, ethnicity, and injury severity. To better understand neurobehavioral functioning after TBI, we need a comprehensive picture of emotional, cognitive, and behavioral symptoms in the context of personal factors that may affect these symptoms. We also need to understand the extent to which these symptoms are specific to TBI, shared across other neurological conditions, or attributable to factors outside of the injury itself. We collected neurobehavioral symptoms via the self-reported Behavioral Assessment Screening Tool (BAST) in a National Cohort of English (n = 2,511) and Spanish speaking (n = 350) community-dwelling adults with and without chronic TBI and other neurological and mental health conditions. The primary focus of the present study was to comprehensively describe neurobehavioral symptoms in adults with and without TBI, broken down by gender and health conditions and then further by age group or educational attainment. As expected, participants with TBI reported more symptoms than Healthy Controls. Regardless of condition, women reported more fatigue, while men reported more substance abuse and impulsivity. Hispanic participants reported more neurobehavioral symptoms than non-Hispanic participants did across health conditions, though primarily Spanish-speakers reported fewer symptoms than English-speakers, suggesting that level of acculturation may contribute to symptom reporting. These data provide a comprehensive characterization of neurobehavioral symptoms in adults with TBI and adults without TBI (healthy controls, adults with other neurological conditions, and adults with mental health conditions).